UJI KOMODITI PADA ALAT PENCACAH SAMPAH ORGANIK (Test of Some Commodities on Organic Waste Grater) - Jonathan Austin Pasaribu; Saipul Bahri Daulay; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2019)
ABSTRACT This research was aimed to test the types of commodity on organic waste grater. The research was conducted to determine the types of commodity to get optimal effectiveness and efficiency of the equipment, the percentage of deposit on the equipment and percentage of losses. The research was conducted using non-factorial randomized block design with types of commodity of corn cob, cocoa pod husk and oil palm empty fruit bunch . Observed parameters were the effective capacity of the grater, yield, percentage of material deposited on the equipment and the percentage of losses. The results showed that the types of commodity had significantly affected the effective capacity, the percentage of material deposited on the grater and the percentage of losses and had no effect on yield. The highest effective capacity was obtained on corn cob i.e. 104,25 kg/hour with the yield of 90%, the percentage of material deposited on the equipment was 5,33% and the percentage of losses was 4,67%. Keywords : The Types of Commodity, Organic Waste Grater. ABSTRAK   Penelitian ini adalah uji komoditi pada alat pencacah sampah organik. Penelitian ini dilakukan untuk mengetahui jenis komoditi yang baik hingga mendapatkan efektifitas dan rendemen yang optimal, serta persentase bahan tertinggal dan persentase kehilangan bahan yang rendah. Penelitian ini dilakukan menggunakan rancangan acak lengkap non faktorial yaitu jenis komoditi tongkol jagung, kulit kakao dan tandan kosong kelapa sawit. Parameter yang diamati adalah kapasitas efektif alat, rendemen, persentase bahan tertinggal dan persentase kehilangan bahan. Hasil penelitian menunjukkan jenis komoditi memberikan pengaruh berbeda sangat nyata terhadap kapasitas efektif alat, persentase bahan tertinggal, dan persentase kehilangan bahan dan berbeda tidak nyata terhadap rendemen. Jenis komoditi yang terbaik dari hasil pengujian ini adalah pada tongkol jagung yaitu kapasitas efektif alat sebesar 104,25 kg/jam dengan rendemen 90%,  persentase bahan tertinggal 5,33%, dan persentase kehilangan bahan 4,67%.   Kata kunci: Jenis Komoditi, Pencacah Sampah Organik.